2018
DOI: 10.1584/jpestics.d17-085
|View full text |Cite
|
Sign up to set email alerts
|

Lack of human relevance for procymidone’s developmental toxicity attributable to species difference in its kinetics and metabolism

Abstract: The agricultural fungicide procymidone can cause external genitalia abnormalities in rats but not monkeys or rabbits. To investigate the relevance of developmental findings in rats to humans, we conducted in vitro plasma protein binding studies, in vitro metabolism (biotransformation) studies using liver S9 fractions and hepatocytes, and in vivo metabolism and excretion studies using chimeric mice with humanized hepatocytes. On the basis of these results, we concluded that the metabolic and excretion profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(32 reference statements)
2
5
0
Order By: Relevance
“…Although data on the urinary excretion of pesticides are generally available in rodents, they have not or have only rarely been described in humans. For example, several authors have highlighted important differences in the metabolic pathways for procymidone between species, including humans using in vitro models and/or chimeric mice with humanized hepatocytes (Abe et al 2018;Tomigahara et al 2018). Carboxylated-procymidone was found to be a major urinary endproduct in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although data on the urinary excretion of pesticides are generally available in rodents, they have not or have only rarely been described in humans. For example, several authors have highlighted important differences in the metabolic pathways for procymidone between species, including humans using in vitro models and/or chimeric mice with humanized hepatocytes (Abe et al 2018;Tomigahara et al 2018). Carboxylated-procymidone was found to be a major urinary endproduct in rats.…”
Section: Discussionmentioning
confidence: 99%
“…pared among species, higher exposure (i.e., AUC and C max ) was observed in rats and rat chimeric mice whereas the exposure was rather low in rabbits, monkeys, and human chimeric mice for both procymidone and its hydroxylated metabolite. In the previous articles on procymidone metabolism in intact rats, 5) delayed T max and higher exposure to the hydroxylated metabolite were caused by the entero-hepatic circulation of its glucuronide.…”
Section: Human Safety Assessment Of the Fungicide Procymidonementioning
confidence: 97%
“…14 C-Labeled procymidone was orally administered to the chimeric mice and other laboratory animals, and the plasma concentrations of procymidone and its metabolites were measured. 5,6) The pharmacokinetic parameters of chimeric mice and other laboratory animals are summarized in Table 1. When the parameters are com-Fig.…”
Section: Human Safety Assessment Of the Fungicide Procymidonementioning
confidence: 99%
“…Procymidone is often used on many crops in China including tomato (Cai et al, 2020; H. Li, et al, 2020; T. T. Li et al, 2020), wheat (Zhou et al, 2020), and mulberry tree (Wei et al, 2016) due to its wide spectrum and high efficiency. A number of studies have shown that procymidone had toxicity to organisms (Abe et al, 2018; Lai et al, 2021; Tarui et al, 2018; Tomigahara et al; 2018, Y. Wu et al, 2018, A. Wu et al, 2021). For instance, procymidone exposure could lead to scoliosis and pericardial edema, and decreased ATPase activity in larval zebrafish (Y. Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%